An Overview of the Influence of Biodiesel, Alcohols, and Various Oxygenated Additives on the Particulate Matter Emissions from Diesel Engines - Puneet Verma; Svetlana Stevanovic; Ali Zare; Gaurav Dwivedi; Thuy Chu Van; Morgan Davidson; Thomas Rainey; Richard J. Brown; Zoran D. Ristovski (Energies, 2019)
Rising pollution levels resulting from vehicular emissions and the depletion of petroleum-based fuels have left mankind in pursuit of alternatives. There are stringent regulations around the world to control the particulate matter (PM) emissions from internal combustion engines. To this end, researchers have been exploring different measures to reduce PM emissions such as using modern combustion techniques, after-treatment systems such as diesel particulate filter (DPF) and gasoline particulate filter (GPF), and alternative fuels. Alternative fuels such as biodiesel (derived from edible, nonedible, and waste resources), alcohol fuels (ethanol, n-butanol, and n-pentanol), and fuel additives have been investigated over the last decade. PM characterization and toxicity analysis is still growing as researchers are developing methodologies to reduce particle emissions using various approaches such as fuel modification and after-treatment devices. To address these aspects, this review paper studies the PM characteristics, health issues, PM physical and chemical properties, and the effect of alternative fuels such as biodiesel, alcohol fuels, and oxygenated additives on PM emissions from diesel engines. In addition, the correlation between physical and chemical properties of alternate fuels and the characteristics of PM emissions is explored.